The Spermatozoa Quality of Kampong Chicken Using Various Diluents - T. Wahyuningsih; R. E. Mirwandhono; Hamdan (Jurnal Peternakan Integratif, 2021)
Kampong chicken has great potential to be developed into superior breed in an effort to support food security and improve farmer welfare. This study aims to determine the effect of adding lactose to free-range chicken semen macroscopically and microscopically. This research was conducted at the Laboratory of the Center for Artificial Insemination at the Food Security and Animal Husbandry Service of North Sumatra Province in October 2020 - January 2021. This study used a Randomized Block Design method with treatment P0 ( Semen control) P1 (Semen with Ringers diluent), P2 (Semen with diluent lactose), P3 (Semen with Ringers diluent + Lactose), macroscopic test and parameters include color, volume, concentration and pH of semen. To determine the quality of spermatozoa can be seen from the motility test, abnormality and viability. The results showed that the use of Ringer + lactose diluent in chicken semen stored for 8 hours at 40C during the study had a very significant effect on spermatozoa motility with values: P0 (52.88% a), P1 (21.64% bc).Â P2 (31.39% b), P3 (19.57% c) respectively and had no significant effect on abnormalities of spermatozoa with values: P0 (6.59% tn), P1 (6.11% tn), P2 (7, 36% tn), P3 (4.4% tn) respectively. As conclusions that the use of ringers + lactose diluent can work well to defend spermatozoa from damage to cell membranes resulting from the elements contained in ringers and lactose solutions which can be used as an energy source when the semen is cold shock during the storage period